Rapid and sensitive drug quantification in tissue sections using matrix assisted laser desorption Ionization-Ion mobility-mass spectrometry profiling - Fresnais, Margaux; Muck, Alexander; Majewsky, Marius; Pfister, Stefan; Haefeli, Walter E.; Burhenne, Jürgen; Longuespée, Rémi (Journal of the American Society for Mass Spectrometry, 2020)
Ion mobility spectrometry (IMS) represents a considerable asset for analytics of complex samples as it allows for rapid mass spectrometric separation of compounds. IMS is even more useful for the separation of isobaric compounds when classical separation methods such as liquid chromatography or electrophoresis cannot be used, e.g., during matrix-assisted laser desorption/ionization (MALDI) analyses of biological surfaces. In the present study, we proved the usefulness of IMS for pharmacological applications of MALDI analyses on tissue sections. To illustrate our proof-of-concept, we used the anthelmintic drug mebendazole (MBZ) as a model. Using this exemplary drug, we demonstrated the possibility of using ion mobility to discriminate a drug in tissues from the biological background that masked its signal at low concentrations. In this proof-of-concept, the IMS mode together with the use of a profiling approach for sample preparation enabled quantification of the model drug MBZ from tissue sections in the concentration range 5 to 5,000 ng/g and with a limit of detection of 1 ng/g of tissue, within 2 h. This study highlights the importance of IMS as a separation method for on-surface quantification of drugs in tissue sections.
Gesehen am 16.04.2020